2007
DOI: 10.1002/pssa.200622571
|View full text |Cite
|
Sign up to set email alerts
|

Luminescence of isoelectronically ion‐implanted SiO2 layers

Abstract: Scanning electron microscopy (SEM) and cathodoluminescence (CL) in combination with scanning transmission electron microscopy (STEM) have been used to investigate thermally grown amorphous silicon dioxide layers implanted isoelectronically with group IV ions (C+, Si+, Ge+, Sn+, Pb+) as well as with group VI ions (O+, S+, Se+). Besides the main luminescent centers in a‐SiO2 layers: the red R luminescence (650 nm; 1.9 eV) of the non‐bridging oxygen hole centers (NBOHC), the blue B (460 nm; 2.7 eV) and the UV (29… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 34 publications
1
8
0
Order By: Relevance
“…From photoluminescence studies, oxygen deficiency centers (ODCs) 73 have been shown to produce emission bands 4.3 eV above the valence band of SiO 2 . 74,75,76,77 Defects in SiO 2 are also observed in the DUV photoemission spectra of glassy SiO 2 and quartz implanted with metals ions. 78,79 In Fig.…”
Section: Resultsmentioning
confidence: 86%
“…From photoluminescence studies, oxygen deficiency centers (ODCs) 73 have been shown to produce emission bands 4.3 eV above the valence band of SiO 2 . 74,75,76,77 Defects in SiO 2 are also observed in the DUV photoemission spectra of glassy SiO 2 and quartz implanted with metals ions. 78,79 In Fig.…”
Section: Resultsmentioning
confidence: 86%
“…The latter one often appears in ion-implanted layers, e.g. Ge + , Sn + , and S + [23] and was attributed to twofold co-ordinated implantation species, but in the present paper it appears as an intrinsic silica decomposition defect associated most probably by OH groups or even dissociated oxygen. As far as we may exclude hydrogen for UV-V luminescence promotion, see [22], oxygen remains as the decisive species for that short wavelength luminescence.…”
Section: Discussionmentioning
confidence: 84%
“…In previous work we did investigate ion-implanted SiO 2 layers: Si + , O + , Ge + in [18]; H + [22], as well as isoelectronic substitutions: S + , Se + for oxygen and C + , Ge + , Sn + , Pb + for silicon [23]. There we applied a post-implantation thermal annealing up to T a = 1100°C and have obtained maximum luminescence for annealing temperatures T a = 80-900°C, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…A closer look in Ref. [12] shows a crystalline structure (lattice) pattern of germanium nanoparticles clearly distinguishable from the amorphous host matrix. The nanocluster sizes are growing with annealing temperature from 1 to 7 nm at T a = 900°C to 3-12 nm at T a = 1100°C as shown in Fig.…”
Section: Resultsmentioning
confidence: 96%
“…These two bands have been attributed to singletsinglet and triplet-singlet transitions, respectively, in isoelectronically twofold coordinated silicon (@Si ÅÅ ), germanium (@Ge ÅÅ ), and tin (@Sn ÅÅ ) [7,10]. A strong violet luminescence band at 3.1 eV is often reported in Ge doped silica and attributed to the Ge-related oxygen deficient center Ge-ODC [9] or low-dimensional Ge nanoclusters imbedded in the silica matrix, [11,12].…”
Section: Introductionmentioning
confidence: 96%